(untitled) (Tribhuvan University Journal of Microbiology, 2024)
Objective: To compare different phenotypic methods used for detecting carbapenem-resistant Enterobacteriaceae and to detect the presence of the OXA-181 gene among them. Methods: A hospital-based cross-sectional prospective study was conducted at Shahid Gangalal National Heart Center, Kathmandu, from September 2021 to March 2022. Altogether, 143 Enterobacteriaceae were isolated from 1042 clinical specimens and subjected to antibiotic susceptibility tests following CLSI guidelines. Several phenotypic methods (Modified Hodge Test (MHT), modified carbapenem inactivation method (mCIM), EDTA-CIM (eCIM) and CarbaNP test were performed for the detection of CRE and the results were compared. In addition, MIC of imipenem was carried out against MDR Enterobacteriaceae using agar dilution method and resistant isolates were also tested by PCR for presence of OXA-181 gene. Results: Among all the Enterobacteriaceae isolates, Klebsiella pneumoniae was the predominant isolate. Gentamycin, nitrofurantoin and carbapenem were found to be most effective, whereas the majority of the isolates were highly resistant to ß-lactam antibiotics along with ciprofloxacin. In total, 43.36% (62/143) isolates were carbapenem-resistant, showing 48.39% (30/62) positivity by MHT, 72.58% (45/62) by mCIM and 61.29% (38/62) by CarbaNP method. The OXA-181 gene was detected in 12 carbapenem-resistant isolates (MIC ≥4 µg/ml), predominantly in K. pneumoniae and E. coli isolates. Conclusion: mCIM is the most effective phenotypic method for detecting carbapenemase production. Presence of OXA-181 gene among clinical isolates is a serious concern, especially in the hospital setting.